The impossible crime - Barnett, Mac (New York : Orchard Books, 2019)
In 1989 someone is threatening to steal the crown jewels, so the Queen of England summons Mac B. to England to protect them--and when they are stolen from a locked dungeon cell, where Mac and Holcroft, one of the warders, are supposed to be guarding them, it is up to Mac to figure out how they were stolen, and whether the thief is the descendant of an Irish soldier-of-fortune who tried to steal them in 1671, or someone else entirely.
Kirkus Review, November 2018
3.9
3-6
440L
Keywords: Crown jewels -- Great Britain -- Juvenile fiction; Theft -- Juvenile fiction; Gems -- Fiction; Stealing -- Fiction; Mystery and detective stories; Humorous stories; Detective and mystery fiction; Humorous fiction